1998
DOI: 10.1200/jco.1998.16.3.953
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of risk factors in stage 4 neuroblastoma patients over the age of one year treated with megatherapy and stem-cell transplantation: a report from the European Bone Marrow Transplantation Solid Tumor Registry.

Abstract: A healthy 37-year-old woman with a familial history of cutaneous melanoma and a recent history (6 months) of atypical nevus was seen in consultation by a dermatologist. Complete skin mapping revealed only an oval, 6 ϫ 4-mm pigmented lesion on her upper left arm that had a history of rapid growth and a variegated chromatic pattern ( Fig 1A). In vivo digital epiluminescence microscopy showed digitated radial streaming, grayish-blue reticular patterns, opaque gypseous alabaster lacunas, brown-black dots on a blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
98
1
11

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(113 citation statements)
references
References 50 publications
3
98
1
11
Order By: Relevance
“…The present study shows that such conditioning regimens can indeed improve the survival of infants with poor prognosis NB. That NB carries a better prognosis in children under 2 years of age has already been demonstrated by the analysis of the EBMT registry, 31 the CCG studies 32 and by the series reported by Hartmann et al 27 Although the number of patients in this latter series is low, the very high DFS emphasizes the prognostic significance of a young age at diagnosis. In poor risk patients, consolidation appears to improve the survival rate all the more when patients are young.…”
Section: Discussionmentioning
confidence: 67%
“…The present study shows that such conditioning regimens can indeed improve the survival of infants with poor prognosis NB. That NB carries a better prognosis in children under 2 years of age has already been demonstrated by the analysis of the EBMT registry, 31 the CCG studies 32 and by the series reported by Hartmann et al 27 Although the number of patients in this latter series is low, the very high DFS emphasizes the prognostic significance of a young age at diagnosis. In poor risk patients, consolidation appears to improve the survival rate all the more when patients are young.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with bone metastasis are classified as stage IV, regardless of other clinical manifestations, and they have a poor prognosis despite high-dose chemotherapy and autologous hematopoietic stem-cell transplantation. 2,3 Clinical and experimental evidence has shown that the tumor growth in bone microenvironment largely depends on the osteoclast activation induced by cytokines and growth factors released from neoplastic cells. [4][5][6][7][8] In the recent years, there have been major advances in understanding how osteoclastogenesis is regulated.…”
mentioning
confidence: 99%
“…Patients with bone metastasis are classified as stage IV, regardless of other clinical manifestations, since the presence of bone/bone marrow metastasis is responsible for poor prognosis despite high-dose chemotherapy and autologous hematopoietic stem cell transplantation. 1 One possible reason for this ominous prognosis is the difficulty in reaching cancer cells that have colonized the bone/bone marrow microenvironment. This suggests the need for effective therapeutic modalities for patients with skeletal metastases based on a precise understanding of the pathophysiology of bone colonization in neuroblastoma.…”
mentioning
confidence: 99%